2018
DOI: 10.3389/fevo.2018.00179
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tropical Cyclone-Generated Deposition on the Sustainability of the Pearl River Marsh, Louisiana: The Importance of the Geologic Framework

Abstract: Shoreline retreat is a tremendously important issue along the coast of the northern Gulf of Mexico, especially in Louisiana. Although this marine transgression results from a variety of causes, the crucial factor is the difference between marsh surface elevation and rising sea levels. In most cases, the primary cause of a marsh's inability to keep up with sea level is the lack of input of inorganic material. Although tropical cyclones provide an important source of such sediment, little effort has been made to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Elemental concentrations (e.g. metal elements) in marsh generally decrease downstream (McCloskey et al ., 2018), while metals (Zr, Ti), mainly derived from igneous rocks (Dill, 2010), are associated with fluvial processes (Dickinson & Gehrels, 2009). Since Br associates with increased localised organics (Ryu et al ., 2018), a high Zr/Br ratio can determine a terrestrial source of inorganic sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Elemental concentrations (e.g. metal elements) in marsh generally decrease downstream (McCloskey et al ., 2018), while metals (Zr, Ti), mainly derived from igneous rocks (Dill, 2010), are associated with fluvial processes (Dickinson & Gehrels, 2009). Since Br associates with increased localised organics (Ryu et al ., 2018), a high Zr/Br ratio can determine a terrestrial source of inorganic sediment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have successfully used XRF analysis to identify marine indicators in coastal sediments, e.g., chlorine (Cl), calcium (Ca), strontium (Sr), and zirconium (Zr) (Ercolani et al, 2015;Liu et al, 2014;McCloskey et al, 2018aMcCloskey et al, , 2018bRamírez-Herrera et al, 2012;Yao et al, 2019Yao et al, , 2020, as well as terrestrial runoff (e.g., iron (Fe), titanium (Ti), and potassium (K) in sedimentary records (Haug et al, 2001;van Soelen et al, 2012;You, 2008). In particular, the chlorine/bromine (Cl/Br) ratio has been used as a marine indicator in sediment-stratigraphic studies in coastal and estuarine environments (Liu et al, 2014;McCloskey et al, 2018aMcCloskey et al, , 2018bYao et al, , 2019Yao et al, , 2020. When a solid or liquid sample is excited by a primary X-ray source, elements present in the sample produce a fluorescent X-ray that is unique for that specific element.…”
Section: X-ray Fluorescencementioning
confidence: 99%
“…Hurricanes normally deposit anomalous sediments through either overwash or flooding. Observations of such anomalous layers have been made in storm deposits from multiple sites that have been impacted by intense storm events (Bianchette et al, 2017;Braun et al, 2017;Liu et al, 2011;McCloskey et al, 2018;Reese et al, 2008;Ryu et al, 2018). The storms disturbed the vegetation in coastal Louisiana as is seen in the diminished pollen percentages of marsh vegetation such as Poaceae, Typha, and Cyperaceae accompanied by an increase in Cheno/Am, which are disturbance indicators.…”
Section: Environmental History Of Bay Jimmy Marshmentioning
confidence: 99%
“…However, some studies suggest that the impact of a storm may not be uniform across marsh environments. For instance, McCloskey et al (2018) found large unsprouted seeds and rhizomes beneath a storm layer that had been deposited by Hurricane Katrina. McCloskey et al (2018) suggest that at their Pearl River Marsh site, in Louisiana, Hurricane Katrina did not erode a significant amount of material, but it deposited sediments.…”
Section: Potential Storm Impactsmentioning
confidence: 99%
See 1 more Smart Citation